Imputação dolosa do crime omissivo impróprio ao empresário em cegueira deliberada - Lucas Pardini Goncalves (2019)
The Dissertation aims to analyze the possibility of recognition of dolus in improperomissive crimes in cases of willful blindness regarding the relevant facts, in Corporate CriminalLaw. For that, it examines willful blindness doctrine in common law and it identifies theproblematic situations of deliberate ignorance in civil law, formulating a concept of willfulblindness. It focuses on improper omissive crimes, analyzing such kind of crime in the corporatefield and the content of dolus in it. Comparing ignorance and mistake, it concludes that they areessentially different and, examining mistake of fact in Brazilian Law, it concludes that willfulblindness does not identify with it. Following a normative theory of dolus, it concludes that,given the right circumstances, it is possible to recognize it in cases of improper omissive crimesin which the agent is willfully blind regarding the relevant facts.